E-Module Development Using the Canva Heyzine Application on Finding Main Ideas in Paragraphs for Grade V Elementary School Students - Amirah, Nazhifa; Arafik, Muh. (Journal of Comprehensive Science, 2024)
This research has four objectives, namely describing the e-module development process, creating e-modules that are valid for material experts and teaching material experts, creating e-modules that are suitable and practical for teachers, and creating e-modules that are interesting to students. Using R&D methods and ADDIE models, as well as interviews, questionnaires, and documentation as data collection instruments, the product received a score of 85.93% from material experts and 98.43% from teaching material experts. In practicality, the product got a result of 90% from teachers. As for attractiveness, the product obtained 100% results from individual trials, 95.55% from small-scale trials, and 95.33% from large-scale trials. Thus, it can be concluded that the e-module of the material seeks the main idea in paragraphs for grade V elementary school students, which has been developed using the Canva Heyzine application and is valid, practical, and interesting to use when learning.